Pelatihan Pengelolaan Uang Saku Bagi Anak-anak Panti Yatim Indonesia Tebet - Rachmawati, Susan; Pramularso, Eigis Yani; Sari, Imelda; Syahyuni, Dedy (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
Money management is an effort related to various activities that can be carried out properly so that it can achieve what has been previously planned in meeting economic needs. Regarding money management, especially pocket money for Yatim Indonesia Tebet Orphanage, there are still problems including lack of understanding to manage finances effectively and efficiently according to needs, the application of pocket money management which is not optimal and the need for improvement in its application including diligent saving, more frugality, and the concept of restraining one's own desires. Therefore, there is a need to find a solution in pocket money management for the residents of Yatim Indonesia Tebet Orphanage. The solution is done by providing training on pocket money management knowledge as a driver of understanding for the children of Yatim Indonesia Tebet Orphanage to be better and wiser in the future regarding their pocket money. The initial method carried out in community service activities is observation, while the implementation stage provides training and understanding of pocket money management by providing direct material and ends with evaluation and monitoring in the form of distributing questionnaires to participants related to community service. The results of the activity are that the participants of the activity stated that 73% stated that they added insight, 71% stated that they added skills and 67% stated that this training activity could provide solutions in solving the problem..